Beyond conventional wage discrimination analysis: Assessing comprehensive wage distributions of males and females using structured additive distributional regression - Alexander Sohn (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In this paper, we propose a new comprehensive framework for analysing wage discrimination. This framework assesses wage discrimination on the grounds of conditional wage distributions (rather than just conditional means), regards the whole population (rather than just those in work) and employs a more general definition of work based on Margaret Reid's "third party criterion" (rather than a definition based on payment). Examining wage discrimination with respect to gender in Germany, we find that gender wage discrimination is exacerbated if considered in such a framework, as women are faced not only with a lower expected pay, but also with a more unequal distribution, lower chances of employment and a higher workload of unpaid activities.
Keywords: C13; C21; D31; J24; J31; 330; Wage Distribution; Discrimination; Gender Inequality; Structured Additive Distributional Regression; Polarisation